Kaznodziejski „pojedynek” Józefa Wereszczyńskiego z Jakubem Wujkiem (na przykładzie marginaliów) - Sitkowa, Anna (Śląskie Studia Polonistyczne, 2015)
The article presents the way in which Józef Wereszczyński (born after 1531, died 1598), a Benedictine abbot from Sieciechów, used, in his work Gościniec pewny niepomiernym moczygębom a omierzłym wydmifuklom świata tego do prawdziwego obaczenia a zbytków) swych pohamowania z Pisma świętego i z rozmaitych autorów zebrany i wydany (1585), one of the sermons of a Jesuit Jakub Wujek (1541–1597), which the latter included in Postylla katoliczna “the greater” (1573–1575; 1584). The focus was on the marginalia – those summarizing the matter and footnotes. It was pointed out that Wereszczyński, besides adopting fragments of a sermon Na tenże dzień Jana świętegokazanie drugie przeciw opilstwu a obżartswu świata dzisiejszego, subjected the marginalia to amplification, substitution and abbreviation practices. Although himself not free from negligence, he also corrected the biblical addresses wrongly identified in Wujek’s Postylla.